Integrating mental skills and strategies into youth sport training: A tool for coaches - Zakrajsek, R. A.; Lauer, E. E.; Bodey, K. J. (International Sport Coaching Journal, 2017)
Youth sport has traditionally focused on developing athletes physically, technically, and tactically; however, it is important to consider the purposeful development of mental and emotional sport skills for these competitors. Youth athletes experience various stressors within their sport participation that impact their ability to successfully manage the sport environment. Youth sport coaches have a tremendous influence on their athletes and are in a position to help them develop the necessary skills to effectively confront the stress they experience. In addition, the International Sport Coaching Framework identifies six primary functions of coaches to help "fulfil the core purpose of guiding improvement and development" of youth athletes (International Council for Coaching Excellence, 2013, p. 16). This article outlines the developmental stage considerations for working with youth athletes and a tool coaches can use to integrate mental skills development strategies into sport practices. Utilizing the evidence-based steps within this article fosters a holistic and developmentally appropriate approach to performance enhancement and personal development, as both are important objectives for youth sport coaches.